The interaction of gold(I) cations with 1,3-dienes. - Sanguramath, R; Hooper, T; Butts, C; Green, M; McGrady, J; Russell, C (2011)
Slip-sliding away: Gold(I) cations bind to only one double bond of a 1,3-diene unit but can glide over the C 4 backbone on a low-activation-energy pathway. However, the binding mode is influenced by substituents on the diene backbone, which also induces a significantly higher barrier to migration. Copyright © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.